How Do Charity Regulators Build Public Trust? - Yang, C; Northcott, D (Wiley, 2021)
Public trust serves as an important foundation for the charity sector, but has been diminishing in many countries. Charity regulation exists to promote public trust in charities, but we know little about how it is implemented by regulators to build public trust. This research examines regulators’ efforts to build public trust in charities by promoting and implementing regulation that increases accountability and transparency requirements. A legal perspective on regulation and trust (Colombo, 2010) is combined with institutional work theory (Lawrence & Suddaby, 2006) to analyse interviews with New Zealand charity regulators and standard setters. The findings detail regulators’ reflexive trust‐building processes and practices and reveal a complex and challenging trust‐building dynamic among regulators, charities and the general public. Regulators’ efforts are revealed to demonstrate a ‘hybrid’ approach to regulation as they expand beyond policing charities’ regulatory compliance, educating charities on how to improve their public accountability and investigating public concerns about charity wrongdoing to also engage in proactive modes of trust‐building that directly target the public. Based on these findings, implications are suggested for regulators in other jurisdictions who seek to build public trust in charities.
Keywords: Charity accountability; Charity regulation; Hybrid regulatory approach; Institutional work; Public trust